Chicken-Pox: «Growing» Up Infection - T. N. Sitnik; L. V. Shteynke; N. V. Gabbasova (Эпидемиология и вакцинопрофилактика)
Chicken pox in the Russian Federation in recent years has maintained a consistently high level of rating in the structure of infectious diseases and the magnitude of economic damage from infectious diseases.Purpose: was to assess the epidemiological features of chicken pox in adults over 18 years in the Voronezh region.Methods. Materials the study was of the form of Federal state statistical supervision over 2006 – 2017 years. The method of retrospective epidemiological analysis was used. Statistical data processing was performed using Microsoft Excel.Results. In recent years, in the Voronezh region there has been an increase in the incidence and hospitalization of adults diagnosed with varicella. In persons older than 18 years, more severe course and complications were observed. Cases of varicella were reported as an infection related to medical care. The sources of infection for nosocomial cases were pregnant women and healthcare professional.Conclusions. In order to prevent introduction and spread of chicken pox in medical organizations of the region it is necessary to consider the immunization of contingents at risk. It requires the introduction of a permanent statistical monitoring of individuals with a diagnosis of «Shingles».